2021
DOI: 10.11606/issn.1679-9836.v100i5p449-454
|View full text |Cite
|
Sign up to set email alerts
|

Análise da taxa de transmissão vertical do HIV e fatores de risco materno-fetais em crianças expostas nascidas em centro de referência do estado de Goiás

Abstract: Objetivos: Estimar a taxa de transmissão vertical do HIV e os fatores de risco materno-fetais em crianças nascidas em 2015 em seguimento durante os anos de 2015 a 2017 no maior centro de referência para tratamento para HIV do estado de Goiás. Métodos: Estudo de coorte retrospectivo de 111 crianças expostas ao HIV nascidas em 2015 de mães HIV positivas. Resultados: Entre as mães, 85 (92,4%) utilizaram TARV durante a gestação. Das 92 crianças que mantiveram seguimento, 4 (4,34%) adquiriram infecção perinatal pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Regarding childbirth, VT occurred in 39.6% (21) of those who underwent prophylaxis during childbirth and in 60.3% (32) of those who did not undergo ART. Several national and international studies have demonstrated that the association of prophylaxis during prenatal care and during childbirth are effective prophylactic measures for the reduction of vertical transmission 1 , 9 , 19 , 28 . A study conducted in Alagoas State, assessing 76 pairs of mother and child, verified that 19.0% of infected pregnant women did not receive ART prophylaxis during pregnancy and 22% did not receive it during childbirth, resulting in a vertical transmission rate of 6.6% 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding childbirth, VT occurred in 39.6% (21) of those who underwent prophylaxis during childbirth and in 60.3% (32) of those who did not undergo ART. Several national and international studies have demonstrated that the association of prophylaxis during prenatal care and during childbirth are effective prophylactic measures for the reduction of vertical transmission 1 , 9 , 19 , 28 . A study conducted in Alagoas State, assessing 76 pairs of mother and child, verified that 19.0% of infected pregnant women did not receive ART prophylaxis during pregnancy and 22% did not receive it during childbirth, resulting in a vertical transmission rate of 6.6% 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, there were approximately 38 million persons living with HIV worldwide, of which 1.8 million were children from 0 to 14 years old 1 . In Brazil, in 2019, there were 43,312 new HIV cases notified on the Notifiable Diseases Data System (SINAN), of which 11,879 were females and 8,268 were pregnant women 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation